TRANSLATION STRATEGIES OF IDIOMATIC EXPRESSIONS IN LOUISA MAY ALCOTT’S LITTLE WOMEN AND ITS INDONESIAN VERSION GADIS-GADIS MARCH - Manurung, Siti Tasya Jelita; Br.Pane, Isli Iriani Indiah; Siregar, Masitowarni (Universitas Islam Sumatera Utara (UISU), 2025)
This qualitative study analyses the strategies used in translating idioms from Louisa May Alcott's novel Little Women into Indonesian Gadis-Gadis March and evaluates the degree of equivalence in the translation. Idioms, as an important element of linguistic and cultural richness, require appropriate strategies to ensure that the original message is conveyed accurately and naturally. Document analysis reveals five main strategies. The most dominant strategy is the use of idioms with similar meanings but different forms (39%), which indicates a priority on preserving meaning and emotional effect rather than adherence to the structure of the source language. The strategy of providing idioms with the same meaning and form (35%) was also used significantly, in an effort to maintain the authenticity of the text. In addition, paraphrasing was applied (22%), focusing on conveying meaning naturally and in accordance with the target cultural context. The strategies of omitting idioms (3%) and borrowing idioms (0%) were rarely used. The distribution of these findings suggests a dominant orientation towards dynamic equivalence, where the main focus of translation is the preservation of meaning, emotional nuance, and cultural impact, rather than literal translation. The results show that effective idiom translation in literary works depends on the selection of strategies that are sensitive to cultural context and capable of maintaining the naturalness of the target language. These findings make a significant contribution to the study of literary translation by clarifying the relationship between the choice of idiom translation strategies and the achievement of dynamic equivalence in fictional texts.